β-Hairpin Peptide Mimics Decrease Human Islet Amyloid Polypeptide (hIAPP) Aggregation - Lesma, Jacopo; Bizet, Faustine; Berardet, Corentin; Tonali, Nicolo; Pellegrino, Sara; Taverna, Myriam; Khemtemourian, Lucie; Soulier, Jean-Louis; van Heijenoort, Carine; Halgand, Frédéric; Ha-Duong, Tâp; Kaffy, Julia; et al. (Frontiers in Cell and Developmental Biology, 2021)
Amyloid diseases are degenerative pathologies, highly prevalent today because they are closely related to aging, that have in common the erroneous folding of intrinsically disordered proteins (IDPs) which aggregate and lead to cell death. Type 2 Diabetes involves a peptide called human islet amyloid polypeptide (hIAPP), which undergoes a conformational change, triggering the aggregation process leading to amyloid aggregates and fibers rich in β-sheets mainly found in the pancreas of all diabetic patients. Inhibiting the aggregation of amyloid proteins has emerged as a relevant therapeutic approach and we have recently developed the design of acyclic flexible hairpins based on peptidic recognition sequences of the amyloid β peptide (Aβ1-42) as a successful strategy to inhibit its aggregation involved in Alzheimer’s disease. The present work reports the extension of our strategy to hIAPP aggregation inhibitors. The design, synthesis, conformational analyses, and biophysical evaluations of dynamic β-hairpin like structures built on a piperidine-pyrrolidine β-turn inducer are described. By linking to this β-turn inducer three different arms i) pentapeptide ii) tripeptide iii) /aza/aza/ pseudotripeptide, we demonstrate that the careful selection of the peptide-based arms from the sequence of hIAPP allowed to selectively modulate its aggregation, while the peptide character can be decreased. Biophysical assays combining, Thioflavin-T fluorescence, transmission electronic microscopy, capillary electrophoresis and mass spectrometry showed that the designed compounds inhibit both the oligomerization and the fibrillization of hIAPP. They are also capable to decrease the aggregation process in the presence of membrane models and to strongly delay the membrane-leakage induced by hIAPP. More generally, this work provides the proof of concept that our rational design is a versatile and relevant strategy for developing efficient and selective inhibitors of aggregation of amyloidogenic proteins.